IMPACT OF FEE-FREE EDUCATION POLICY ON STUDENT ENROLLMENT AND QUALITY OF SECONDARY EDUCATION IN NYAMAGANA DISTRICT, TANZANIA - Rodrick, Kazinduki; M. Mwila, Prospery (PANDU : Jurnal Pendidikan Anak dan Pendidikan Umum, 2025)
This study investigates the impact of the fee-free education (FFE) policy on the quality of education in secondary schools within Nyamagana District. Specifically, it examines how the surge in student enrollment due to the FFE policy affects educational quality. A convergent parallel design within a mixed-methods approach was employed, combining both quantitative and qualitative methods to leverage the strengths of each and mitigate their respective weaknesses.The sample consisted of 104 respondents: 93 teachers, 5 headteachers, 5 ward educational officers, and 1 district quality assurance officer. Both probability and non-probability sampling techniques were used due to the study population's characteristics. Data were gathered through interviews and questionnaires.The findings revealed that 80% of headteachers were aware of the FFE policy, with all headteachers able to explain it correctly. However, 81% of teachers were aware of the policy. Those with limited understanding attributed this to factors such as lack of involvement in the policy's initiation, confusion from other financial contributions within schools, insufficient funding, and negative attitudes from parents towards the teaching profession.Additionally, the study identified significant changes following FFE implementation, including increased student enrollment and attendance. However, these changes have presented challenges to maintaining educational quality.In conclusion, while the FFE policy has boosted enrollment, it has created challenges for delivering quality education. The study recommends that the government allocate more resources and improve funding mechanisms to support the effective implementation of the FFE policy.